Electrocardiographic changes among beta-thalassemic major patients in ibn al-baladi thalassemia center-Baghdad - Mohammed, Suhad Jassim; Al-Lami, FarisH.; Hussein, Mousa Qasim (AL-Kindy College Medical Journal, 2013)
Background :Thalassemia is an autosomaldisease of the haemoglobin. Two types ofthalassemia are recognized: thalassemia majorand thalassemia intermedia.The most serious cardiac complication inthalassemia major is due to multiple bloodtransfusions rather than the disease itself, whichis due to iron overload.Cardiomyopathy is the most common cardiacdefect that occurs with iron overload. Pricarditis,congestive heart failure and arrhythmias are dueto hemosidrosis and chronic aneamia.Aim of the study: to demonstrate the prevalenceand types of electrocardiographic changes amongthalassemic patients with aged over ten years old.